ISOLATION AND IDENTIFICATION OF MOLD AND YEAST IN THE GROWTH MEDIA OF BLACK SOLDIER FLY MAGGOTS FROM A MIX OF SHEEP FECES, DAIRY WASTE SLUDGE, AND ORGANIC KITCHEN WASTE - E., ANISA; BADRUZZAMAN, D. Z.; HARLIA, E. (Majalah Ilmiah Peternakan, 2024)
Sheep feces, dairy waste sludge, and organic kitchen waste are potential growth media for BSF maggots. The process of degradation organic matter by maggot BSF is aided by various microorganisms. Microorganisms that play a role in the degradation process of organic compounds include molds and yeasts. This study was conducted to determine the number and type of molds and yeasts obtained from the growth media of BSF maggot in a mix of sheep feces, dairy waste sludge, and organic kitchen waste. This study used an experimental method with data anal- yzed descriptively. The results showed that the number of molds and yeasts decreased. The average number of mold colonies before degradation was 7,15 x 104 cfu/ml ± 1,6 and after degradation was 2,69 x 104 cfu/ml ± 0,7. While the average number of yeast colonies before degradation was 9,00 x 104 cfu/ml ± 2,1 and after was 3,50 x 104 cfu/ ml ± 0,55. The molds that were successfully isolated and identified in maggot media samples included Aspergillus sp., Cladosporium sp., Mucor sp., Neurospora sp., Penicillium sp., and, Rhizopus sp., while the yeasts that were successfully isolated and identified in the maggot media samples included Candida sp., Saccharomyces sp., and Zygosaccharomyces sp.